"Rebuild by Design” in New York City: Introducing the Context of the Competition and Considering a Literature Review on Disaster Planning and Resilience Theory - Fleming, Billy (Ri-Vista. Research for landscape architecture, 2017)
“Rebuild by Design” was a four-stage, interdisciplinary design competition aimed at bolstering the resilience of the New York region after Hurricane Sandy. The competition included ten multi-disciplinary teams, each of which worked within a distinct neighbourhood or city within the Sandy-affected region. Six of these teams were awarded a disproportionate share of 1 billion in Community Development Block Grant (CDBG)-Disaster Recovery funding. Though the competition received considerable praise from the popular press, it remains a relatively unexplored topic amongst planning and design scholars. This paper investigates why “Rebuild by Design” emerged as an option in the aftermath of Sandy and why the competition sought to focus on resilience-making in lieu of more conventional post-disaster concerns through a review of the literature on Disaster Planning and Resilience Theory